Exploration of Pilobolus sp. Fungi from Various Livestock Manures in Kedung Pacul Village, Klaten - Mahardhika, Wahyu Aji; Akmaliyah, Rizna; Diana, Milsa Solva; Listyowati, Sri (Bioma : Berkala Ilmiah Biologi, 2024)
Pilobolus is a coprophilous fungus belonging to the Zygomycota. Pilobolus sp. is called a coprophilous fungus because it can live in animal feces. The uniqueness of this fungus is that it can shoot its spores, so Pilobolus sp. is called a shotgun fungus. Pilobolus sp. exhibits a phototropism mechanism in which the sporangium shoots spores in the direction of light. Pilobolus has a unique living habitat, namely in the manure of herbivores such as cows, goats, sheep, etc. This habit of life may seem terrible to us, but fungi like Pilobolus sp. are very important in life because they are a type of decomposer, capable of breaking down organic matter from dead living things. So the purpose of this study was to observe the spores produced by the fungus Pilobolus sp.  (a fungus in animal waste). The method used was to cultivate the fungus Pilobolus sp. for seven days on various animal wastes placed in jam bottles. The results showed that the Pilobolus sp. fungus grew on various media of animal feces, such as horses, cows, goats, and pigs, with different growth times, and there were also spores shot on the glass walls that had been perforated.